Thermal front dynamics and the correlation with Sardinella Lemuru catches in the Bali Strait - Hendrik Anggi Setyawan; Bogi Budi Jayanto; Ayu Retno Wardhani (Politeknik Negeri Sambas, 2025)
The Bali Strait is a marine area rich in lemuru fish (Sardinella lemuru), making it a potential fishery commodity in Indonesia. Sustainable management of lemuru fish populations in the Bali Strait is crucial for maintaining ecosystem balance and ensuring the sustainability of the fishing industry in the region. This study aimed to identify the thermal fronts in the Bali Strait and the relationship between thermal fronts and lemuru fish production. This research was conducted using monthly sea surface temperature and surface current data from the CMEMS for the year 2023, along with lemuru production data from PPN Pengambengan. An edge detection method was employed to determine thermal fronts. The results showed that sea surface temperatures ranged from 24.9°C to 29°C. The meridional movement from North to South dominates the Bali Strait surface currents. Thermal fronts were observed throughout the year, with weak fronts dominating during the west monsoon and transition season I, whereas strong fronts intensified during the southeast monsoon. However, the correlation between thermal fronts and lemuru catch was very weak (r=-0.047442), suggesting that thermal fronts are not the primary factor influencing lemuru catch.